AUDIT SISTEM INFORMASI PADA SISTEM INFORMASI AKADEMIK PERSPEKTIF PROSES BISNIS INTERNAL BALANCED SCORECARD DAN STANDAR COBIT 4.1 (STUDI KASUS: STMIK SINAR NUSANTARA SURAKARTA) - Setiyowati, Sri Harjanto (STMIK Sinar Nusantara, 2015)
Academic Information Systems in STMIK Sinar Nusantara Surakarta handling processes include financial, KRS online, New Student registration. In managing the process, using several application modules that implement the concept of Enterprise Resource Planning (ERP), wherein execution of the application have not been audited to ensure alignment of IT with business objectives. To measure how far the alignment between business processes, applications, and business enterprise.Strategies for information systems auditing standards COBIT 4.1, where the calculation of which can represent the level of maturity of a company. While service quality has a major influence on academic activities, the audit focused on the user's perspective of the Balanced Scorecard. The results of this audit stated that the level of process maturity. Process which indicates that the organization has a formal standard procedures and written, in the absence of supervision to perform the procedure, allowing the occurrence of many irregularities. Keywords : sistem informasi akademik, COBIT , tingkat kematangan, Balanced Scorecard .